Formation of the department of pedagogyand educational development problems at the Belarusian State University - Ershova, Olga I. (University Pedagogical Journal, 2026)
This article is devoted to the creation of the Belarusian State University in the 1920–1930s a structural unit uniting teachers of pedagogical disciplines in order to ensure their educational, scientific and educational-methodological activities. It is shown that its first form was a methodological and pedagogical subject commission, formed in the 1924/25 academic year at the faculty of education. As a result of changes in the organisational structure of the university, a department of pedagogy was created on the basis of this subject commission in 1930.